Relationship between Internet Addiction and Life Satisfaction Among Students: Case of Albania - Agaj, Desara (European Journal of Multidisciplinary Studies, 2023)
Nowadays, human life has become very intensive. Since we live in the age of technology and we are part of a global world, the Internet has become an indispensable part of everyday life, bringing many benefits to people. However, its excessive use can often leave to negative consequences that affect the psychological well-being of the individual as well as the evaluation and general perception that the individual has of his life. This article comes as a result of studies in the wake of further research in the field of Internet addiction among teenagers and students in our country. The purpose of this article is to study the relationship between internet addiction among students aged 18-21 in Albania and their level of life satisfaction, as well as specifically the impact that life satisfaction has on internet addiction. In this study participated 268 students from three universities in Albania. Data were collected through online completion of Young’s (1998) Internet Addiction Questionnaire, and Diener’s (1985) Life Satisfaction Questionnaire. The study highlighted the fact that there is a negative, statistically significant relationship between Internet addiction and the level of life satisfaction in the target group included in the study.